2021
DOI: 10.1111/iji.12525
|View full text |Cite
|
Sign up to set email alerts
|

Matchmaker, matchmaker make me a match: Opportunities and challenges in optimizing compatibility of HLA eplets in transplantation

Abstract: The development of donor‐specific antibodies (DSAs) is a major complication in transplantation, which is associated with inferior graft survival, impaired quality of life, and increased healthcare costs. DSA develop upon recognition of nonself HLA by the recipient's immune system. HLA molecules contain epitopes, which are the surface regions of HLA molecules recognized by antibodies. HLAMatchmaker is an algorithm for assessing donor:recipient HLA compatibility at the level of structurally defined HLA targets c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…14 Human leukocyte antigens (HLA) corresponding to MHC class II are HLA‐DP, HLA‐DM, HLA‐DOA, HLA‐DOB, HLA‐DQ, and HLA‐DR. While for MHC class I, there is a dominant allele in the population worldwide (HLA‐A*02; 29–46%), this is not the case for any MHC class II encoding genes 15 . As a result, there is a large inter‐individual variation in HLA and the peptides that are presented.…”
Section: The Targets: Specific Antigen Receptors On Lymphocytes and F...mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Human leukocyte antigens (HLA) corresponding to MHC class II are HLA‐DP, HLA‐DM, HLA‐DOA, HLA‐DOB, HLA‐DQ, and HLA‐DR. While for MHC class I, there is a dominant allele in the population worldwide (HLA‐A*02; 29–46%), this is not the case for any MHC class II encoding genes 15 . As a result, there is a large inter‐individual variation in HLA and the peptides that are presented.…”
Section: The Targets: Specific Antigen Receptors On Lymphocytes and F...mentioning
confidence: 99%
“…While for MHC class I, there is a dominant allele in the population worldwide (HLA-A*02; 29-46%), this is not the case for any MHC class II encoding genes. 15 As a result, there is a large inter-individual variation in HLA and the peptides that are presented. Each T cell expresses a TCR with distinct specificity, which results from genomic rearrangement of V, D, and J genes in their TCR loci to create a unique first exon that encodes the variable domain.…”
Section: Thetarg E Ts:s Pecificanti G En Recep Tor Sonlympho C Y Te S...mentioning
confidence: 99%
“…HLA eplets are small configurations of surface-exposed amino acids within a 3-3.5 Ångstrom (Å) radius (3,4) and resemble the functional epitope, which generally determines the specificity of the antibody through interaction with the complementaritydetermining region 3 (CDR3) of the heavy chain of the antibody (5)(6)(7). Consideration of HLA eplets instead of HLA antigens may not only refine HLA matching strategies, resulting in decreased DSA formation, but also expand the donor pool for highly sensitized patients and facilitate personalized immunosuppressive treatment based on immunological risk evaluation (8). Indeed, several studies have shown that eplet mismatches are correlated with DSA formation, graft rejection and graft loss (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown that eplet mismatches are correlated with DSA formation, graft rejection and graft loss (9)(10)(11)(12)(13)(14). However, as eplets have been theoretically defined, their clinical relevance needs to be validated by antibody verification (8,15). Although antibody-verified eplet mismatches have been demonstrated to correlate with DSA formation and graft survival (13,14), recent reports also indicated that there are still clinically relevant eplets which have not been antibodyverified yet (13,16).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated an association between eplet mismatches and formation of dnDSA (12)(13)(14)(15)(16)(17). However, not all theoretically defined eplets are immunogenic and thus verification of actual interactions with antibodies is needed to determine the clinically relevant eplets (18)(19)(20). For HLA class I, a large number of eplets has been verified by several different methods (21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%